Concrete and preparation method thereof
By using aluminum-hydrotalcite composition and microcapsule reinforcement in concrete, the porous structure and closed-porous structure are formed, and the problem of insufficient corrosion resistance of aerated concrete in the prior art is solved, and good insulation and resistance are achieved. Corrosion performance.
Patent Information
- Application Number
- CN202411075259.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-07
AI Technical Summary
It is difficult for existing concrete to combine both aerating and corrosion resistance, resulting in a significant reduction in the corrosion resistance of aerated concrete and it is unable to have good thermal insulation and corrosion resistance at the same time.
Using an aluminum-hydrotalc composition and a microcapsule enhancer, hydrogen is formed by reacting aluminum with calcium hydroxide to form a porous structure, hydrotalc fixes chloride ions, and a closed-porous structure is formed in the concrete through microcapsules to enhance corrosion resistance.
It improves the thermal insulation and sound insulation effect of concrete, while significantly enhancing corrosion resistance, preventing chloride ions from penetration, and improving overall mechanical properties and corrosion resistance.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of concrete, and in particular to concrete and a preparation method thereof. Background Art
[0002] At present, with the development of the construction and decoration industries, the functional requirements for concrete are becoming more abundant. Among them, aerated concrete and anti-corrosion concrete are widely used in various fields. Aerated concrete has good thermal insulation and sound absorption effects, and is widely used in industrial and civil buildings as load-bearing and non-load-bearing structural materials and thermal insulation materials. Anti-corrosion concrete is mainly used in underground projects or coastal buildings to reduce the corrosion of chloride ions on the steel bars in the concrete.
[0003] For existing concrete, it is difficult to combine aeration and corrosion resistance to obtain a concrete material that combines the advantages of both. Generally speaking, aerated concrete has a large number of pore structures, which makes it easy for water with a high concentration of chloride ions to penetrate into the concrete, thereby causing a significant decrease in the corrosion resistance of the concrete. Summary of the invention
[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a concrete and a preparation method thereof.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] A concrete comprising the following raw materials in parts by weight:
[0007] 200-300 parts of cement;
[0008] Aggregate 1800-2000 parts;
[0009] 32-45 parts of fly ash;
[0010] 65-80 parts of mineral powder;
[0011] 80-200 parts of admixture;
[0012] 5-15 parts of water reducing agent;
[0013] 150-230 parts of water;
[0014] The admixture comprises an aluminum-hydrotalcite composite, and the mass ratio of the aluminum material to the hydrotalcite is 15-20:1.
[0015] By adopting the above technical scheme, cement is the main cementitious material of concrete, which forms a cementitious substance through hydration reaction to provide strength and stability. Aggregates include fine aggregates (such as sand) and coarse aggregates (such as gravel), which provide volume stability and compressive strength of concrete, reduce cement dosage and reduce costs. Fly ash can improve the workability, durability and impermeability of concrete. Mineral powder can improve the early and late strength of concrete, improve durability and resistance to chemical erosion. Water reducer is a chemical admixture that can reduce water consumption while maintaining the workability of concrete, improve the strength and durability of concrete, and improve the fluidity and construction performance of concrete. The aluminum in the aluminum-hydrotalcite composite admixture generates hydrogen in concrete by reacting with calcium hydroxide and water. These hydrogens form fine bubbles in the slurry, making the concrete present a porous structure. The presence of bubbles gives concrete good thermal insulation and sound insulation effects, because the gas has a low thermal conductivity and can effectively block heat conduction and sound transmission. Hydrotalcite is a layered double hydroxide that effectively fixes chloride ions mainly through its layered structure and ion exchange capacity, and the positive charge between the hydrotalcite layers can effectively adsorb negatively charged chloride ions to prevent them from being lost. After the aluminum and hydrotalcite are combined, the aluminum reacts to produce gas, and the hydrotalcite material on the aluminum will also accumulate at the gas production position, so that the bubbles and hydrotalcite are evenly distributed in the concrete. At this time, the pores in the aerated concrete are all attached with hydrotalcite. When the chloride ion penetrant enters the concrete, the penetrant mainly penetrates along the pores flowing in the concrete, and the hydrotalcite can perform ion exchange to fix the chloride ions more specifically, making it more difficult for the chloride ions to enter the deeper areas inside the concrete, greatly improving the corrosion resistance of the concrete.
[0016] Furthermore, the preparation method of the aluminum-hydrotalcite composition comprises the following steps:
[0017] A1: Preparation of Mg 2+ and NO3 - The molar ratio of 1:5 to 7 is a reaction solution, and the pH of the reaction solution is controlled to be 9 to 10;
[0018] A2: The surface of the aluminum raw material is polished and pickled, and then cut into aluminum sheets with a size of 1 cm×1 cm×0.5 mm;
[0019] A3: Mix the aluminum sheet and the reaction solution and react at 95°C for 36-48h;
[0020] A4: Rinse the aluminum sheet after reaction with distilled water and dry it.
[0021] Furthermore, the aluminum-hydrotalcite composition is in powder form, and the average particle size is controlled to be 0.1 to 0.5 mm.
[0022] Furthermore, the raw materials also include 120 to 300 parts by weight of a microcapsule enhancer, the microcapsule enhancer including a first microcapsule and a second microcapsule, the first microcapsule being a microcapsule with 4,5-epoxytetrahydrophthalic acid diglycidyl ester as a core material and urea-formaldehyde resin as a wall material; the second microcapsule being a microcapsule with pentaerythritol tetraester and benzyldimethylamine as a core material and urea-formaldehyde resin as a wall material.
[0023] By adopting the above technical solution, a microcapsule reinforcing agent is also added to the concrete. The microcapsule reinforcing agent is divided into a first microcapsule and a second microcapsule, wherein the core material in the first microcapsule and the core material in the second microcapsule can undergo a curing reaction after contact, so that the 4,5-epoxytetrahydrophthalic acid diglycidyl ester in the first microcapsule is cured to form epoxy resin filling. During the curing process of concrete, the microcapsule is broken due to stress such as extrusion. At this time, the flow holes in the pores formed by the aluminum-hydrotalcite composition are more likely to allow the core material in the microcapsule to flow in, so that most of the flow holes become closed holes, while some of the closed holes have less core material flowing in, and the pores will not be completely filled. This hinders the flow of chloride ions in the concrete, greatly weakens the conductivity of the concrete, and greatly improves the corrosion resistance of the concrete. The resistance of chloride ions in the process of penetrating from the surface to the inside is greatly increased, and each pore generated by the aeration of aluminum basically contains hydrotalcite, so that the corrosion resistance of the concrete is greatly improved while retaining the pores. In addition, the core material will increase the overall compactness of the concrete during the flow process, thereby enhancing the various mechanical properties of the concrete and further making the movement of chloride ions more difficult.
[0024] Furthermore, the mass ratio of pentaerythritol tetraester to benzyldimethylamine is 8-11:1.
[0025] Furthermore, the preparation method of the first microcapsule comprises the following steps:
[0026] B1: prepare an emulsifier made of ammonium chloride, sodium dodecylbenzene sulfonate, resorcinol and water, and heat it to 40-45°C;
[0027] B2: dissolving the core material of 4,5-epoxytetrahydrophthalic acid diglycidyl ester in an emulsifier to obtain a core material emulsion;
[0028] B3: Dissolve urea and formaldehyde in deionized water at a mass ratio of 1:2, and adjust the solution to alkalinity using triethylamine to obtain a wall material solution;
[0029] B4: Drop the wall material solution into the core material emulsion, and at the same time add citric acid to make it acidic, and stir at 60-70℃ for 3-5h;
[0030] B5: The solution after the reaction is filtered to obtain white powder, which is then washed and dried to obtain the first microcapsule.
[0031] Furthermore, the preparation method of the second microcapsule comprises the following steps:
[0032] C1: prepare an emulsifier made of ammonium chloride, sodium dodecylbenzene sulfonate, resorcinol and water, and heat it to 40-45°C;
[0033] C2: Evenly mix pentaerythritol tetraester and benzyl dimethylamine and dissolve them in an emulsifier to obtain a core material emulsion;
[0034] C3: dissolving urea and formaldehyde in deionized water at a mass ratio of 1:2, and adjusting the solution to alkalinity using triethylamine to obtain a wall material solution;
[0035] C4: drip the wall material solution into the core material emulsion, and at the same time add citric acid to acidify it, and stir at 60-70℃ for 3-5h;
[0036] C5: The solution after the reaction is filtered to obtain white powder, which is then washed and dried to obtain the second microcapsule.
[0037] Furthermore, the microcapsule reinforcing agent and the aluminum-hydrotalcite composition are pre-mixed to prepare an integrated additive, and the preparation method comprises the following steps:
[0038] D1: mixing a microcapsule reinforcing agent, an aluminum-hydrotalcite composition, polyester staple fibers, a binder and water to obtain a slurry;
[0039] D2: Lay the slurry on the grid, and perform vacuum suction on the side of the grid away from the slurry, and press the slurry with a pressing plate;
[0040] D3: Dry the compacted slurry at 50-60°C;
[0041] D4: Cut the dried slurry into block particles with a length, width and height of 1 to 2 cm.
[0042] By adopting the above technical scheme, the microcapsule enhancer and the aluminum-hydrotalcite composition are pre-mixed to prepare an integrated additive, so that the distribution of the microcapsule enhancer and the aluminum-hydrotalcite composition in the concrete is more uniform, and the microcapsule enhancer and the aluminum-hydrotalcite composition tend to be distributed together, that is, compared with other aggregates, mineral powders and other components, the distance between the microcapsule enhancer and the aluminum-hydrotalcite composition is closer, and the microcapsule enhancer and the aluminum-hydrotalcite composition as a whole are uniformly distributed in the concrete together with other aggregates, mineral powders and other components. This makes the pore structure formed by the microcapsule enhancer and the aluminum-hydrotalcite composition closer, and the core material flowing out of the two microcapsules in the microcapsule enhancer is easier to close the pore structure formed by the aeration of the aluminum-hydrotalcite composition, so that the pores in the concrete form more closed pores, reduce the ability of chloride ions to flow through the pores, and improve the corrosion resistance. Secondly, the resin formed by the core materials flowing out of the two microcapsules in the microcapsule reinforcer and the hydrotalcite in the pores can form a closer match, so that the barrier effect of the resin and the fixing effect of the hydrotalcite are better synergistic, thereby effectively reducing the penetration of chloride ions and improving the corrosion resistance of concrete.
[0043] Furthermore, the vacuum degree of the vacuum suction is controlled to be -100 to -80 kPa, and the vacuum suction time is 10 to 30 minutes.
[0044] A method for preparing concrete comprises the following steps:
[0045] S1: Mix cement, aggregate, mineral powder and fly ash of concrete in proportion for 30 seconds;
[0046] S2: Add the water reducing agent to the mixture after stirring in S1 and stir for 20 seconds;
[0047] S3: Add the admixture into the mixture stirred in S2 and continue stirring for 3 to 4 minutes;
[0048] S4: pouring and curing the mixture stirred in S3 to obtain concrete.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] The present invention adds an aluminum-hydrotalcite composite admixture, and the hydrogen generated by aluminum during the concrete forming process forms fine bubbles, making the concrete porous, thereby enhancing the thermal insulation and sound insulation effects of the concrete; and the hydrotalcite fixes chloride ions through its special layered structure and ion exchange capacity, thereby enhancing the corrosion resistance of the concrete. Secondly, by adding two microcapsules in the microcapsule enhancer, the core materials after the rupture during the concrete forming process contact and solidify with each other to form an epoxy resin, the pore structure is optimized, the closed-pore property is improved, and the flow of chloride ions is further hindered under the premise that the porosity is not too small, thereby improving the corrosion resistance of the concrete. Furthermore, the microcapsule enhancer is pre-mixed with the aluminum-hydrotalcite composite, and the distribution is more uniform, further improving the sealing effect and corrosion resistance of the pores. Finally, the overall performance of the concrete is improved, the mechanical properties are enhanced, the chloride ion penetration resistance is increased, and the corrosion resistance is improved. DETAILED DESCRIPTION
[0051] The present invention is described in detail below in conjunction with embodiments.
[0052] Example 1
[0053] The present invention discloses a concrete comprising the following raw materials in parts by weight:
[0054] 200 parts of cement;
[0055] Aggregate 1800 parts;
[0056] 32 parts of fly ash;
[0057] 65 parts of mineral powder;
[0058] 80 parts of admixture;
[0059] 5 parts of water reducing agent;
[0060] 150 parts water;
[0061] The admixture comprises an aluminum-hydrotalcite composite, the aggregate is machine-made sand, the mineral powder is blast furnace slag powder, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0062] The preparation method of the aluminum-hydrotalcite composition comprises the following steps:
[0063] A1: Weigh Mg(NO3)2 and dissolve it in ammonium nitrate solution. Stir evenly to prepare Mg 2+ and NO3 - The molar ratio of 1:6 is 1:6, and the pH of the reaction solution is adjusted to 9 with aqueous ammonia;
[0064] A2: The surface of the aluminum raw material is polished and pickled, and then cut into aluminum sheets with a size of 1 cm×1 cm×0.5 mm;
[0065] A3: Mix the aluminum sheet and the reaction solution and react at 95°C for 36 hours;
[0066] A4: Rinse the aluminum sheet after reaction with distilled water and dry it.
[0067] The aluminum-hydrotalcite composition was ground into powder, and the average particle size was controlled to be 0.5 mm. The weight ratio of aluminum material to hydrotalcite in the aluminum-hydrotalcite composition was 15:1.
[0068] A method for preparing concrete comprises the following steps:
[0069] S1: Mix cement, aggregate, mineral powder and fly ash of concrete in proportion for 30 seconds;
[0070] S2: Add the water reducing agent to the mixture after stirring in S1 and stir for 20 seconds;
[0071] S3: Add the admixture into the mixture stirred in S2 and continue stirring for 3 minutes;
[0072] S4: pouring and curing the mixture stirred in S3 to obtain concrete.
[0073] Example 2
[0074] The present invention discloses a concrete comprising the following raw materials in parts by weight:
[0075] 300 parts of cement;
[0076] Aggregate 2000 parts;
[0077] 45 parts of fly ash;
[0078] 80 parts of mineral powder;
[0079] 200 parts of admixture;
[0080] 15 parts of water reducing agent;
[0081] 230 parts of water;
[0082] The admixture comprises an aluminum-hydrotalcite composite, the aggregate is machine-made sand, the mineral powder is blast furnace slag powder, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0083] The preparation method of the aluminum-hydrotalcite composition comprises the following steps:
[0084] A1: Weigh Mg(NO3)2 and dissolve it in ammonium nitrate solution. Stir evenly to prepare Mg 2+ and NO3 - The molar ratio of 1:6 is 1:6, and the pH of the reaction solution is adjusted to 9 with aqueous ammonia;
[0085] A2: The surface of the aluminum raw material is polished and pickled, and then cut into aluminum sheets with a size of 1 cm×1 cm×0.5 mm;
[0086] A3: Mix the aluminum sheet and the reaction solution and react at 95°C for 36 hours;
[0087] A4: Rinse the aluminum sheet after reaction with distilled water and dry it.
[0088] The aluminum-hydrotalcite composition was ground into powder, and the average particle size was controlled to be 0.5 mm. The weight ratio of aluminum material to hydrotalcite in the aluminum-hydrotalcite composition was 15:1.
[0089] A method for preparing concrete comprises the following steps:
[0090] S1: Mix cement, aggregate, mineral powder and fly ash of concrete in proportion for 30 seconds;
[0091] S2: Add the water reducing agent to the mixture after stirring in S1 and stir for 20 seconds;
[0092] S3: Add the admixture into the mixture stirred in S2 and continue stirring for 3 minutes;
[0093] S4: pouring and curing the mixture stirred in S3 to obtain concrete.
[0094] Example 3
[0095] The present invention discloses a concrete comprising the following raw materials in parts by weight:
[0096] 250 parts of cement;
[0097] Aggregate 1900 parts;
[0098] 38 parts of fly ash;
[0099] Mineral powder 72 parts;
[0100] 140 parts of admixture;
[0101] 10 parts of water reducing agent;
[0102] 190 parts of water;
[0103] The admixture comprises an aluminum-hydrotalcite composite, the aggregate is machine-made sand, the mineral powder is blast furnace slag powder, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0104] The preparation method of the aluminum-hydrotalcite composition comprises the following steps:
[0105] A1: Weigh Mg(NO3)2 and dissolve it in ammonium nitrate solution. Stir evenly to prepare Mg 2+ and NO3 -The molar ratio of 1:6 is 1:6, and the pH of the reaction solution is adjusted to 9 with aqueous ammonia;
[0106] A2: The surface of the aluminum raw material is polished and pickled, and then cut into aluminum sheets with a size of 1 cm×1 cm×0.5 mm;
[0107] A3: Mix the aluminum sheet and the reaction solution and react at 95°C for 36 hours;
[0108] A4: Rinse the aluminum sheet after reaction with distilled water and dry it.
[0109] The aluminum-hydrotalcite composition was ground into powder, and the average particle size was controlled to be 0.5 mm. The weight ratio of aluminum material to hydrotalcite in the aluminum-hydrotalcite composition was 15:1.
[0110] A method for preparing concrete comprises the following steps:
[0111] S1: Mix cement, aggregate, mineral powder and fly ash of concrete in proportion for 30 seconds;
[0112] S2: Add the water reducing agent to the mixture after stirring in S1 and stir for 20 seconds;
[0113] S3: Add the admixture into the mixture stirred in S2 and continue stirring for 3 minutes;
[0114] S4: pouring and curing the mixture stirred in S3 to obtain concrete.
[0115] Example 4
[0116] The present invention discloses a concrete comprising the following raw materials in parts by weight:
[0117] 250 parts of cement;
[0118] Aggregate 1900 parts;
[0119] 38 parts of fly ash;
[0120] Mineral powder 72 parts;
[0121] 140 parts of admixture;
[0122] 10 parts of water reducing agent;
[0123] Microcapsule enhancer 120-300;
[0124] 190 parts of water;
[0125] The admixture comprises an aluminum-hydrotalcite composite, the aggregate is machine-made sand, the mineral powder is blast furnace slag powder, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0126] The preparation method of the aluminum-hydrotalcite composition comprises the following steps:
[0127] A1: Weigh Mg(NO3)2 and dissolve it in ammonium nitrate solution. Stir evenly to prepare Mg 2+ and NO3 - The molar ratio of 1:6 is 1:6, and the pH of the reaction solution is adjusted to 9 with aqueous ammonia;
[0128] A2: The surface of the aluminum raw material is polished and pickled, and then cut into aluminum sheets with a size of 1 cm×1 cm×0.5 mm;
[0129] A3: Mix the aluminum sheet and the reaction solution and react at 95°C for 36 hours;
[0130] A4: Rinse the aluminum sheet after reaction with distilled water and dry it.
[0131] The aluminum-hydrotalcite composition was ground into powder, and the average particle size was controlled to be 0.5 mm. The weight ratio of aluminum material to hydrotalcite in the aluminum-hydrotalcite composition was 20:1.
[0132] The microcapsule enhancer includes a first microcapsule and a second microcapsule in a mass ratio of 1:1, wherein the first microcapsule is a microcapsule with 4,5-epoxytetrahydrophthalic acid diglycidyl ester as a core material and urea-formaldehyde resin as a wall material. The second microcapsule is a microcapsule with pentaerythritol tetraester and benzyl dimethylamine as a core material and urea-formaldehyde resin as a wall material. The mass ratio of pentaerythritol tetraester to benzyl dimethylamine is 10:1.
[0133] The preparation method of the first microcapsule comprises the following steps:
[0134] B1: an emulsifier prepared by mixing ammonium chloride, sodium dodecylbenzene sulfonate, resorcinol and water in a mass ratio of 1:1:1:400 and heating the mixture to 40°C;
[0135] B2: dissolving a core material of 4,5-epoxytetrahydrophthalic acid diglycidyl ester with a mass of 1 / 10 of the emulsifier in the emulsifier to obtain a core material emulsion;
[0136] B3: Dissolve urea and formaldehyde in deionized water at a mass ratio of 1:2, and adjust the solution to alkalinity using triethylamine to obtain a wall material solution;
[0137] B4: Add the wall material solution to the core material emulsion and add citric acid to make it acidic, and stir at 60℃ for 3h;
[0138] B5: The solution after the reaction is filtered to obtain white powder, which is then washed and dried to obtain the first microcapsule.
[0139] The preparation method of the second microcapsule comprises the following steps:
[0140] C1: an emulsifier prepared by mixing ammonium chloride, sodium dodecylbenzene sulfonate, resorcinol and water in a mass ratio of 1:1:1:400 and heating the mixture to 40°C;
[0141] C2: pentaerythritol tetraester and benzyl dimethylamine are uniformly mixed in proportion and dissolved in an emulsifier to obtain a core material emulsion;
[0142] C3: dissolving urea and formaldehyde in deionized water at a mass ratio of 1:2, and adjusting the solution to alkalinity using triethylamine to obtain a wall material solution;
[0143] C4: drip the wall material solution into the core material emulsion, and at the same time add citric acid to acidify it, and stir at 60℃ for 3h;
[0144] C5: The solution after the reaction is filtered to obtain white powder, which is then washed and dried to obtain the second microcapsule.
[0145] A method for preparing concrete comprises the following steps:
[0146] S1: Mix cement, aggregate, mineral powder and fly ash of concrete in proportion for 30 seconds;
[0147] S2: Add the water reducing agent to the mixture after stirring in S1 and stir for 20 seconds;
[0148] S3: Add the admixture and microcapsule enhancer to the mixture stirred in S2 and continue stirring for 3 minutes;
[0149] S4: pouring and curing the mixture stirred in S3 to obtain concrete.
[0150] Example 5
[0151] The present invention discloses a concrete comprising the following raw materials in parts by weight:
[0152] 250 parts of cement;
[0153] Aggregate 1900 parts;
[0154] 38 parts of fly ash;
[0155] Mineral powder 72 parts;
[0156] 140 parts of admixture;
[0157] 10 parts of water reducing agent;
[0158] Microcapsule enhancer 120-300;
[0159] 190 parts of water;
[0160] The admixture comprises an aluminum-hydrotalcite composite, the aggregate is machine-made sand, the mineral powder is blast furnace slag powder, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0161] The preparation method of the aluminum-hydrotalcite composition comprises the following steps:
[0162] A1: Weigh Mg(NO3)2 and dissolve it in ammonium nitrate solution. Stir evenly to prepare Mg 2+ and NO3 - The molar ratio of 1:6 is 1:6, and the pH of the reaction solution is adjusted to 9 with aqueous ammonia;
[0163] A2: The surface of the aluminum raw material is polished and pickled, and then cut into aluminum sheets with a size of 1 cm×1 cm×0.5 mm;
[0164] A3: Mix the aluminum sheet and the reaction solution and react at 95°C for 36 hours;
[0165] A4: Rinse the aluminum sheet after reaction with distilled water and dry it.
[0166] The aluminum-hydrotalcite composition was ground into powder, and the average particle size was controlled to be 0.5 mm. The weight ratio of aluminum material to hydrotalcite in the aluminum-hydrotalcite composition was 18:1.
[0167] The microcapsule enhancer includes a first microcapsule and a second microcapsule in a mass ratio of 1:1, wherein the first microcapsule is a microcapsule with 4,5-epoxytetrahydrophthalic acid diglycidyl ester as a core material and urea-formaldehyde resin as a wall material. The second microcapsule is a microcapsule with pentaerythritol tetraester and benzyl dimethylamine as a core material and urea-formaldehyde resin as a wall material. The mass ratio of pentaerythritol tetraester to benzyl dimethylamine is 10:1.
[0168] The preparation method of the first microcapsule comprises the following steps:
[0169] B1: an emulsifier prepared by mixing ammonium chloride, sodium dodecylbenzene sulfonate, resorcinol and water in a mass ratio of 1:1:1:400 and heating the mixture to 40°C;
[0170] B2: dissolving a core material of 4,5-epoxytetrahydrophthalic acid diglycidyl ester with a mass of 1 / 10 of the emulsifier in the emulsifier to obtain a core material emulsion;
[0171] B3: Dissolve urea and formaldehyde in deionized water at a mass ratio of 1:2, and adjust the solution to alkalinity using triethylamine to obtain a wall material solution;
[0172] B4: Add the wall material solution to the core material emulsion and add citric acid to make it acidic, and stir at 60℃ for 3h;
[0173] B5: The solution after the reaction is filtered to obtain white powder, which is then washed and dried to obtain the first microcapsule.
[0174] The preparation method of the second microcapsule comprises the following steps:
[0175] C1: an emulsifier prepared by mixing ammonium chloride, sodium dodecylbenzene sulfonate, resorcinol and water in a mass ratio of 1:1:1:400 and heating the mixture to 40°C;
[0176] C2: pentaerythritol tetraester and benzyl dimethylamine are uniformly mixed in proportion and dissolved in an emulsifier to obtain a core material emulsion;
[0177] C3: dissolving urea and formaldehyde in deionized water at a mass ratio of 1:2, and adjusting the solution to alkalinity using triethylamine to obtain a wall material solution;
[0178] C4: drip the wall material solution into the core material emulsion, and at the same time add citric acid to acidify it, and stir at 60℃ for 3h;
[0179] C5: The solution after the reaction is filtered to obtain white powder, which is then washed and dried to obtain the second microcapsule.
[0180] The microcapsule reinforcing agent and the aluminum-hydrotalcite composition are pre-mixed to prepare an integrated additive, and the preparation method comprises the following steps:
[0181] D1: A microcapsule reinforcing agent, an aluminum-hydrotalcite composition, polyester staple fibers, a binder and water are mixed to obtain a slurry; the binder is a polyamide-epichlorohydrin resin.
[0182] D2: Lay the slurry on the grid, and perform vacuum suction on the side of the grid away from the slurry, and press the slurry with a pressing plate; the vacuum degree of vacuum suction is controlled to -100kPa, and the vacuum suction time is 10min;
[0183] D3: drying the compacted slurry at 50°C;
[0184] D4: Cut the dried slurry into block particles with a length, width and height of 1 cm.
[0185] A method for preparing concrete comprises the following steps:
[0186] S1: Mix cement, aggregate, mineral powder and fly ash of concrete in proportion for 30 seconds;
[0187] S2: Add the water reducing agent to the mixture after stirring in S1 and stir for 20 seconds;
[0188] S3: Add the integrated additive to the mixture stirred in S2 and continue stirring for 3 minutes;
[0189] S4: pouring and curing the mixture stirred in S3 to obtain concrete.
[0190] Comparative Example
[0191] The difference between Comparative Example 1 and Example 1 is that no aluminum-hydrotalcite composite admixture is added to the concrete raw materials.
[0192] Detection Methods
[0193] The sealed specimen was immersed in a 5% NaCl solution for 5 days, then dried in an oven at (50±2)℃ for 1 day, and finally placed in an air environment for 5 days. - After 8 cycles of erosion under the erosion mechanism, the cubic specimen was ground and sampled on its erosion surface using a profile grinder (GENMANNPF-1100 model), with samples taken every 2 mm at a depth of 0-10 mm from the surface, and every 5 mm at a depth of 11-25 mm from the surface. All powders were passed through a 0.63 mm metal sieve, and the powders under the sieve were dried at (100±5)°C. The solution was prepared in accordance with the Technical Specifications for the Detection of Chloride Ion Content in Concrete (JGJ / T322-2013). After the preparation was completed, the solution was left to stand for 24 hours, and the mass fractions of free chloride ions and total chloride ions were detected using AgNO3 potentiometric titration and an automatic titrator (ZDJ-5B model).
[0194]
[0195]
[0196]
[0197]
[0198]
[0199]
[0200] The thermal conductivity of the dried sample was determined in accordance with GB / T32064-2015 “Transient Plane Heat Source Test Method for Thermal Conductivity and Thermal Diffusivity of Building Materials”. The instrument was the DRE-2C thermal conductivity tester of Xiangtan Xiangke Instrument Co., Ltd., and the test block size was 40 mm×40 mm×40 mm.
[0201]
[0202] Conclusion: It can be seen from the above test results that the concrete prepared by the present invention has good thermal insulation effect, and the corrosion resistance, that is, the resistance to chloride ion permeability, is greatly improved. Moreover, when the microcapsule reinforcing agent and the aluminum-hydrotalcite composite admixture are added at the same time in the present invention, the corrosion resistance, that is, the resistance to chloride ion permeability of the concrete can be further improved while basically maintaining the thermal insulation effect of the concrete. Furthermore, premixing the microcapsule reinforcing agent and the aluminum-hydrotalcite composite admixture into an integrated additive can optimize the distribution of the two in the concrete, thereby improving the corrosion resistance, that is, the resistance to chloride ion permeability of the concrete.
[0203] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 200-300 parts of cement; Aggregate 1800-2000 parts; 32-45 parts of fly ash; 65-80 parts of mineral powder; 80-200 parts of admixture; 5-15 parts of water reducing agent; 150-230 parts of water; Wherein, the admixture comprises an aluminum-hydrotalcite composition, and the mass ratio of aluminum to hydrotalcite is 15-20:1; The raw materials also include 120 to 300 parts by weight of a microcapsule enhancer, wherein the microcapsule enhancer includes a first microcapsule and a second microcapsule, wherein the first microcapsule is a microcapsule with 4,5-epoxytetrahydrophthalic acid diglycidyl ester as a core material and urea-formaldehyde resin as a wall material; and the second microcapsule is a microcapsule with pentaerythritol tetraester and benzyl dimethylamine as a core material and urea-formaldehyde resin as a wall material. The microcapsule reinforcing agent and the aluminum-hydrotalcite composition are pre-mixed to prepare an integrated additive, and the preparation method comprises the following steps: D1: mixing a microcapsule reinforcing agent, an aluminum-hydrotalcite composition, polyester staple fibers, a binder and water to obtain a slurry; D2: Lay the slurry on the grid, and perform vacuum suction on the side of the grid away from the slurry, and press the slurry with a pressing plate; D3: Dry the compacted slurry at 50-60°C; D4: Cut the dried slurry into block particles with a length, width and height of 1 to 2 cm.
2. A concrete according to claim 1, characterized in that: The preparation method of the aluminum-hydrotalcite composition comprises the following steps: A1: Preparation of Mg 2+ and NO3 - The molar ratio of 1:5 to 7 is a reaction solution, and the pH of the reaction solution is controlled to be 9 to 10; A2: The surface of the aluminum raw material is polished and pickled, and then cut into aluminum sheets with a size of 1 cm×1 cm×0.5 mm; A3: Mix the aluminum sheet and the reaction solution and react at 95°C for 36-48h; A4: Rinse the aluminum sheet after reaction with distilled water and dry it.
3. A concrete according to claim 2, characterized in that: The aluminum-hydrotalcite composition is in powder form, and the average particle size is controlled to be 0.1-0.5 mm.
4. The concrete according to claim 1, characterized in that: The mass ratio of the pentaerythritol tetraester to benzyl dimethylamine is 8-11:
1.
5. The concrete according to claim 1, characterized in that: The preparation method of the first microcapsule comprises the following steps: B1: prepare an emulsifier made of ammonium chloride, sodium dodecylbenzene sulfonate, resorcinol and water, and heat it to 40-45°C; B2: dissolving the core material of 4,5-epoxytetrahydrophthalic acid diglycidyl ester in an emulsifier to obtain a core material emulsion; B3: Dissolve urea and formaldehyde in deionized water at a mass ratio of 1:2, and adjust the solution to alkalinity using triethylamine to obtain a wall material solution; B4: Drop the wall material solution into the core material emulsion, and at the same time add citric acid to make it acidic, and stir at 60-70℃ for 3-5h; B5: The solution after the reaction is filtered to obtain white powder, which is then washed and dried to obtain the first microcapsule.
6. The concrete according to claim 1, characterized in that: The preparation method of the second microcapsule comprises the following steps: C1: prepare an emulsifier made of ammonium chloride, sodium dodecylbenzene sulfonate, resorcinol and water, and heat it to 40-45°C; C2: Evenly mix pentaerythritol tetraester and benzyl dimethylamine and dissolve them in an emulsifier to obtain a core material emulsion; C3: dissolving urea and formaldehyde in deionized water at a mass ratio of 1:2, and adjusting the solution to alkalinity using triethylamine to obtain a wall material solution; C4: drip the wall material solution into the core material emulsion, and at the same time add citric acid to acidify it, and stir at 60-70℃ for 3-5h; C5: The solution after the reaction is filtered to obtain white powder, which is then washed and dried to obtain the second microcapsule.
7. The concrete according to claim 1, characterized in that: The vacuum degree of the vacuum suction is controlled to be -100 to -80 kPa, and the vacuum suction time is 10 to 30 minutes.
8. A method for preparing concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Mix cement, aggregate, mineral powder and fly ash of concrete in proportion for 30 seconds; S2: Add the water reducing agent to the mixture after stirring in S1 and stir for 20 seconds; S3: Add the integrated additive to the mixture stirred in S2 and continue stirring for 3 to 4 minutes; S4: pouring and curing the mixture stirred in S3 to obtain concrete.
Citation Information
Patent Citations
Layered film for forming concrete-surface-coating layer, concrete construction material, and method for producing same
CN106458774A
Durable concrete and preparation method thereof
CN113135701A
Recycled concrete and preparation method thereof
CN116003033A
Sprayed concrete super-early-strength low-resilience admixture, preparation method thereof and concrete
CN116332555A
Mortar composition for repairing and reinforcing concrete structures, and method of repairing and reinforcing concrete structures using the same
KR101627548B1
